학령기 아동의 비유언어 이해 특성 - 박선희(Sun Hee Park); 박민아(Min Ah Park) (언어치료연구, 2018)
목적: 이 연구의 목적은 학령기 아동의 비유언어에 대한 이해의 특성이 어떠한지를 살펴보고, 학년간의 차이가있는지 알아보기 위함에 연구의 목적이 있다. 방법: 연구 대상으로는 일반 초등학교에 재학 중인 2~5학년 54 명으로 선정하였다. 비유언어 검사 도구는 은유, 직유, 관용어, 속담으로 구분하고 은유 유형은 지각적 은유와심리적 은유로, 직유 유형은 외연적 직유, 내포적 직유로 세분화하여 유형별 각 8문항씩 총 48문항으로 구성하였다. 결과: 첫째, 저학년 집단과 고학년 집단 모두 직유, 은유, 속담, 관용어의 순서로 높은 점수를 얻었다. 둘째, 은유에서는 저학년과 고학년 집단 모두 지각적 은유가 심리적 은유보다 더 높은 점수를 보였고, 직유에서도 저학년 및 고학년 집단 모두 외연적 직유가 내포적 직유보다 더 높은 점수를 보였으며. 관용과 속담 역시고학년 집단이 저학년 집단보다 높은 점수를 얻었다. 셋째, 비유언어 오류 분석에서 저학년 집단은 비유언어의모든 유형에서 사전적 의미의 문자적 오답율이 관련 없는 오답율에 비하여 높았다. 고학년 집단은 지각적 은유, 내포적 직유, 관용어에서는 사전적 의미의 문자적 오답율이 관련 없는 오답율보다 높았으나, 심리적 은유와속담에서는 관련 없는 오답율이 사전적 의미의 문자적 오답율에 비하여 더 높았다. 결론: 학령기 아동의 은유에서는 지각적 은유가 심리적 은유보다 더 쉽게 이해되고, 직유에서는 외연적 직유를 내포적 직유보다 더 잘이해하였다. 은유, 직유, 관용과 속담에 있어서도 학년이 높을수록 이해도가 높은 편으로 나타났다. Purpose: The purpose of this study is to identify the characteristics of the figurative language of school-aged children and to investigate the difference between the grade levels. Methods: The subjects of this study were 54 children in the second to fifth grades attending a general elementary school. The figurative language tasks consisted of metaphor, simile, idioms, and proverbs. Metaphor items were classified into perceptual metaphor and psychological metaphor, while simile items were subdivided into extrinsic simile and intrinsic simile, and consisted of 48 items, each of 8 items by type. Results: First, both the lower and upper grades received high scores in the order of simile, metaphor, proverbs, and idioms. Second, in metaphor understanding, perceptual metaphors shower higher scores than psychological metaphors in both the lower and upper groups. In simile understanding, the score of the upper grade group was higher than that of the lower grade group, and both extrinsic simile and intrinsic simile were shown more than the lower grade group. In idiom understanding and proverb understanding, the score of the upper grade group was higher than that of the lower grade group. Third, in figurative language error analysis, the lower grade group had higher literal error rates than irrelevant error rates in all items. The upper grade group had higher literal error rates than irrelevant error rates in perceptual metaphor, intrinsic simile, and idioms, but irrelevant error rates higher than literal error rates in psychological metaphor and proverb. Conclusions: Metaphor, perceptual metaphor, and psychological metaphor were better developed as grade increased. In simile, extrinsic simile was understood more easily than intrinsic simile; extrinsic simile and intrinsic simile were better developed as grade increased. Idioms and proverbs were also developed as grade increased. KCI Citation Count: 2